Thermal robustness of signaling in bacterial chemotaxis - Aliaksiuk, Volha; Jakovljević, Vladimir; Vladimirov, Nikita; Carvalho, Ricardo; Paster, Eli; Ryu, William S.; Meir, Yigal; Wingreen, Ned S.; Kollmann, Markus; Sourjik, Victor (Cell, 2011)
Temperature is a global factor that affects the performance of all intracellular networks. Robustness against temperature variations is thus expected to be an essential network property, particularly in organisms without inherent temperature control. Here, we combine experimental analyses with computational modeling to investigate thermal robustness of signaling in chemotaxis of Escherichia coli, a relatively simple and well-established model for systems biology. We show that steady-state and kinetic pathway parameters that are essential for chemotactic performance are indeed temperature-compensated in the entire physiological range. Thermal robustness of steady-state pathway output is ensured at several levels by mutual compensation of temperature effects on activities of individual pathway components. Moreover, the effect of temperature on adaptation kinetics is counterbalanced by preprogrammed temperature dependence of enzyme synthesis and stability to achieve nearly optimal performance at the growth temperature. Similar compensatory mechanisms are expected to ensure thermal robustness in other systems.